The gender dependent influence of sodium bicarbonate supplementation on anaerobic power and specific performance in female and male wrestlers - Durkalec-Michalski, K.; Zawieja, E. E.; Zawieja, B. E.; Michalowska, P.; Podgórski, T. (Scientific Reports, 2020)
The aim of this study was the assessment of progressive low-dose sodium bicarbonate (NaHCO3) supplementation on the anaerobic indices in two bouts of Wingate tests (WT) separated by wrestling-specific performance test and assessing the gender differences in response. Fifty-one (18 F) wrestlers completed a randomized trial of either a NaHCO3 (up to 100 mg·kg-1) or a placebo for 10 days. Before and after treatment, athletes completed an exercise protocol that comprised, in sequence, the first WT1, dummy throw test (DT), and second WT2. The number of completed throws increased significantly in males from 19.3 ± 2.6 NaHCO3pre to 21.7 ± 2.9 NaHCO3post. DeltaWT2-WT1 improved particularly in the midsection of 30-s WT on NaHCO3. However, no significant differences were found in peak power (PP), power drop (PD) and average power (AP) (analyzed separately for each WT), and DeltaWT2-WT1 in PP and PD. Interaction with gender was significant for AP, PP and PD, every second of WT1 and WT2, as well as DT test. In conclusion, our study suggests that the response to NaHCO3 may be gender-specific and progressive low-dose NaHCO3 supplementation allows the advantageous strengthening of wrestling-specific performance in males. It can also lead to maintenance of high anaerobic power mainly in the midsection of the 30-s Wingate test.